KARAKTERISTIK SIFAT FISIKO-KIMIA DAN THERMAL SERTA PENERIMA ORGANOLEPTIK KUE SAGON BERBASIS TEPUNG PISANG - Achmat Sarifudin; Riyanti Ekafitri (Jurnal Penelitian Pascapanen Pertanian, 2015)
physical, chemical and thermal properties of the sagon cake as weparameter are physical properties including degree of whiteness and its sensory acceptability parameters. The design experimentriplicate measurements for each observation parameters. The obtcoconut grated 1:  2 were most favored by respondents.